2014
DOI: 10.1007/s00167-014-3302-0
|View full text |Cite
|
Sign up to set email alerts
|

Graft maturity of the reconstructed anterior cruciate ligament 6 months postoperatively: a magnetic resonance imaging evaluation of quadriceps tendon with bone block and hamstring tendon autografts

Abstract: The maturity of quadriceps tendon with bone block was better in comparison with hamstring 6 months after anatomic SB ACL reconstruction. This study is clinically relevant in that modifying the individual rehabilitation according to the extent of graft maturity may be necessary to optimize patient function and prevent re-injury of the ACL graft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 30 publications
5
78
1
1
Order By: Relevance
“…The lower the value of the SNQ g, the lower the water content of the graft and the more mature the ACL graft was. 35,36…”
Section: Radiographic and Magnetic Resonance Image Evaluationmentioning
confidence: 99%
“…The lower the value of the SNQ g, the lower the water content of the graft and the more mature the ACL graft was. 35,36…”
Section: Radiographic and Magnetic Resonance Image Evaluationmentioning
confidence: 99%
“…Concerns regarding the slower healing involved with tendon to bone incorporation have limited its use as a first line graft in the elite athletic population [59,60]. In addition, some studies have suggested that the failure rate with hamstring autografts may be somewhat higher than bone-patella-bone autograft [61].…”
Section: Graft Choicementioning
confidence: 99%
“…Amerika Birleşik Devletleri'nde yaklaşık olarak her yıl iki yüz bin üzerinde ÖÇB yaralanması meydana gelirken yüz bin üzerinde ÖÇB rekonstrüksiyonu ameliyatı yapılmaktadır (2,3). ÖÇB rekonstrüksiyonu ameliyatında kullanılan her birisinin avantaj ve dezavantajları olan birçok greft tipi mevcuttur (4,5). Hastadan alınarak yapılan otogreft ile ÖÇB rekonstrüksiyonu donör saha morbiditesi ve cerrahi travma gibi riskler barındırmaktadır (6)(7)(8).…”
Section: Introductionunclassified